Fostering SME's co-development of innovative projects in biotech clusters: Extending the sets of enablers for the knowledge creation process. (November 2021) - Ferasso, Marcos; Grenier, Corinne
Abstract: We explore the linkage of specific sets of enablers for the knowledge-creation process (KCP) mobilized in innovative projects co-developed by biotech SMEs and the role of industrial clusters in easing the access to enablers. Two French and one Brazilian high-tech SMEs belonging to two biotechnological clusters were investigated. Deductive and inductive approaches were applied in a complementary manner. Findings revealed a larger set of enablers at the company's level than predicted in the literature. We identified two sets of KCP enablers at the cluster's level, classified as open access and restricted access, which are used for different purposes and simultaneously. These dynamics enabled the studied SMEs to improve their co-developed innovative projects in a more effective way. Data also revealed that the enablers that benefit SMEs are more likely provided by the cluster organisations. Highlights: We explored the enablers of KCP in high-techs' co-developed projects. The role of industrial cluster in offering externalities to inner SMEs was identified. A larger and more diversified multilevel set of enablers was identified. Identified dynamics enabled SMEs to improve co-developed projects in a more effective way.